1998
DOI: 10.1175/1520-0442-11.8.2078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vegetation in the Dynamics of West African Monsoons

Abstract: The focus of this paper is the role of meridional distribution of vegetation in the dynamics of monsoons and rainfall over West Africa. A moist zonally symmetric atmospheric model coupled with a simple land surface scheme is developed to investigate these processes. Four primary experiments have been carried out to examine the sensitivity of West African monsoons to perturbations in the meridional distribution of vegetation. In the control experiment, the authors assume a distribution of vegetation that resemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(99 citation statements)
references
References 63 publications
2
95
1
1
Order By: Relevance
“…Eltahir and Gong 1996;Zheng and Eltahir 1998) have highlighted the role of complex surface-atmosphere interactions to explain the maintenance of the convective activity and the strong monsoon flux south of the convective band (i.e. around 5°N) nearly 90 days after the SHL onset whereas the WAHL weakens and the meridional gradient of the geopotential diminishes.…”
Section: The Onset Of the Saharan Heat Low And Its Link With The Westmentioning
confidence: 99%
“…Eltahir and Gong 1996;Zheng and Eltahir 1998) have highlighted the role of complex surface-atmosphere interactions to explain the maintenance of the convective activity and the strong monsoon flux south of the convective band (i.e. around 5°N) nearly 90 days after the SHL onset whereas the WAHL weakens and the meridional gradient of the geopotential diminishes.…”
Section: The Onset Of the Saharan Heat Low And Its Link With The Westmentioning
confidence: 99%
“…Nevertheless in most cases, these experiments showed a decrease in precipitation and an increase in temperature over the region as a result of deforestation. Another set of experiments have investigated the issue of the effects of subtropical African deforestation and land degradation on the West Africa monsoon, using both global and regional climate models (RCMs) (Charney, 1975;Zheng and Eltahir, 1998;Clark et al ., 2001;Abiodun et al ., 2007;Zeng and Neelin, 1999;Dirmeyer and Shukla, 1994;Henderson-Sellers and Gornitz, 1984;Werth and Avissar, 2005). They showed that the land surface conditions can affect the development of the West Africa Monsoon through the modification of moist static energy gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of changed vapor f lows due to land-cover change in East Asia have affected the behavior of the East Asian Monsoon, including a weakening of the summer monsoon low-pressure system and an increase in irregular northerly f low (12,19). Modeled vegetation changes for agricultural expansion in West Africa have shown potentially dramatic impacts on rainfall in the African monsoon circulation, especially through deforestation along the southern coast, because this deforestation decreases the vapor f low into the region (20).…”
mentioning
confidence: 99%